Educating the Disadvantaged The Task School Districts Face - Passow, A. Harry ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
The terms "educationally disadvantaged" and "compensatory education" are defined in many ways. "Compensation" implies a deficit which must be overcome, but there is little agreement on where the deficiency is located--in the child, his family or home, his school, or all of these. In general, it is agreed that school districts with large concentrations of children from disadvantaged backgrounds have substantially lower academic achievement levels and higher dropout rates, but there is no consensus on the causes for these and other differentials in educational performance. Since the 1960's, a variety of Federal and State legislation has been enacted to provide compensatory programs and services, but these efforts have met with varied successes and failures. The 30,000 Title I projects, for example, reflected multiple goals and multiple treatments which are not easily converted into overarching objectives or successful program models. This multiplicity has complicated any effort to evaluate compensatory programs, but twenty years of compensatory programs have taught us that the immediate goal should be to raise the achievement levels of more disadvantaged students. A survey of literature which attempted to generalize about the lessons of compensatory education makes it possible to justify increased expenditures in the following areas: (1) early childhood programs; (2) staff development and in-service education; (3) pull-out vis-a-vis regular class instruction; (4) appropriate instructional materials and resources; (5) provisions for children with limited English; (6) programs for disadvantaged high school students; (7) programs for the disadvantaged gifted; (8) parent participation programs; and (9) recruiting and retaining of teachers. (KH)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Compensatory Education; Economically Disadvantaged; Educational Finance; Educational Policy; Educationally Disadvantaged; Elementary Secondary Education; Equal Education; Student Needs; Elementary Secondary Education Act Title I; Opinion Papers; Reports, General